Biosynthesis of Silver Microparticles Using Spondias Dulcis Fruit Peel Extract and Its Antibacterial Activity - Girsang, Thereshia Margaretta; Purba, Elisabeth; Simamora, Adela Rosalia; Sihombing, Chatrina Yohana; Inabuy, Marchella; Tahya, Candra Yulius (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
In recent decades, the overuse and misuse of antibiotics, along with various social and economic factors, have accelerated the spread of antibiotic-resistant bacteria, including Klebsiella pneumoniae and Pseudomonas aeruginosa, both of which are Gram-negative pathogenic bacteria. Silver particles (AgPs) have garnered significant research interest over the years due to their diverse biological activities, particularly their antibacterial properties. The green synthesis method for silver particles involves synthesizing silver metal particles using natural materials derived from organisms such as plants, resulting in particles that are less harmful to human cells but highly toxic to pathogenic bacteria. Kedondong (Spondias dulcis) is a tropical fruit widely grown in South and Southeast Asia. The peels of this fruit often become organic waste with limited utility. To explore the potential of kedondong fruit peels, this study investigated the synthesis of silver particles using their extract. The ethanolic extract of kedondong fruit peels was analyzed using LC-MS/MS-QTOF, identifying 5 alkaloids, 21 flavonoids, and 17 terpenoid compounds. The total flavonoid and phenolic contents of the extract were determined to be 1.8918 and 12.8104 mg/g of extract, respectively. The silver particles synthesized in this study had an average size of 4641.97 micrometers and a zeta potential of 40.2 mV, as determined by PSA, and were confirmed as silver particles through P-XRD phase analysis. These silver particles exhibited strong antibacterial activity against P. aeruginosa, with an inhibition zone diameter of 19.43 mm, and moderate activity against K. pneumoniae, with an inhibition zone diameter of 11.50 mm, at a suspension concentration of 10 mg/mL. Notably, the P. aeruginosa strain used in this experiment was resistant to the antibiotic amoxicillin.